Implementation of Compliance with Non-Smoking Area Policy at Rejosari Health Center, Tenayan Raya District, Pekanbaru City: Implementasi Kepatuhan Terhadap Kebijakan Kawasan Tanpa Rokok (Ktr) Di Puskesmas Rejosari Kecamatan Tenayan Raya Kota Pekanbaru - Indah Mutiara Yuri; M.Dedi Widodo; Zainal Abidin; Ahmad Hanafi; Yanwir Kamal (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
To realize the highest degree of health and realize a healthy Indonesia and reduce the number of conscientiousness caused by cigarettes, the government issued a Joint Regulation of the Minister of Health and Minister of Home Affairs No.188 / Menkes / PB / I / 2011 No. 7 of 2011 concerning Guidelines for Non-Smoking Areas. And the Mayor of Pekanbaru issued a regulation on non-smoking areas, namely number 39 of 2014. The researcher's problem is how to implement the KTR policy at the Rejosari Health Center in Pekanbaru City. This study aims to determine the Implementation of Compliance with the No Smoking Area (KTR) Policy at the Rejosari Health Center, Tenayan Raya District, Pekanbaru City in 2022.The type of research carried out is qualitative with a descriptive method, a scientific approach to which the phenomenological approach is used. The data collection method was carried out by observation and in-depth interviews with 7 informants, namely the head of the Public health center, Public health center officers, security, and visitors. The results of this study show that the implementation of compliance with the No Smoking Area Policy at the Rejosari Health Center has not been carried out properly. the implementation of socialization that has not been effective to officers and visitors which makes the lack of public knowledge about KTR in Public health center, and there is no Special Team to supervise the Public health center environment, the readiness of the implementer has not fully demonstrated an attitude that supports the policy of non-smoking areas in puskesmas, there are still findings of visitors who smoke in the Public health center environment this is because there is no strict sanction from the Public health center. and have not prepared guidelines and commitments. It is recommended to the Head of the Rejosari Health Center to provide knowledge to all officers and visitors of the Rejosari Health Center in Pekanbaru City regarding the No Smoking Area at the Public health center, conduct socialization, form a special KTR Team and make strict sanctions, namely making written regulations and making commitments.